Resocializing digital water transformations: Outlining social science perspectives on the digital water journey. (2nd February 2021) - Hoolohan, Claire; Amankwaa, Godfred; Browne, Alison L.; Clear, Adrian; Holstead, Kirsty; Machen, Ruth; Michalec, Ola; Ward, Sarah
Abstract: Digital water transformation is often written about as though universally desirable and inevitable, capable of addressing the multifaceted socioecological challenges that water systems face. However, there is not widespread reflection on the complexities, tensions and unintended consequences of digital transformation, its social and political dimensions are often neglected. This article introduces case studies of digital water development, bringing examples of technological innovation into dialogue with literature and empirical research from across the social sciences. We examine how Big Data affects our observations of water in society to shape water management, how the Internet of Things becomes involved in reproducing unjust water politics, how digital platforms are entangled in the varied sociocultural landscape of everyday water use, and how opensource technologies provide new possibilities for participatory water governance. We also reflect on regulatory developments and the possible trajectories of innovation resulting from public‐private sector interactions. A socially and politically informed view of digital water is essential for just and sustainable development, and the gap between industry visions of digital water and research within the social sciences is inhibitive. Thus, the analysis presented in this article provides a novel, pluralistic perspective on digital water development and outlines what is required for more inclusive future scholarship, policy and practice. This article is categorized under: Human Water Abstract : Digital water transformation is uncertain, complex and contested. Here insights from the social sciences are applied to explore innovations in the water sector, highlighting issues of politics, justice and uncertainty, to establish a more socially informed view of digital water. ( Source: Author original artwork ).